LOCAL VALUES-BASED ORGANIZATIONAL CULTURE: A STUDY OF BALINESE CULTURAL VALUES EFFECTS ON COOPERATIVES EMPLOYEE PERFORMANCE AND JOB STRESS IN BALI - Ni WayanSitiari; Ni LuhAnikPuspaningsih; IB.Ag.Dharmenegara (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
In Indonesia, cooperatives have a main role as a pillar of people's economic development. Regarding cooperatives development, the Government of Bali faces problems of human resources low quality and the low level of cooperatives linkage. Like other organizations in general, the cause of low performance and stress on cooperative employees is the discrepancy of organizational culture with local cultural values. There are three local cultural values adopted by cooperatives organizational culture in Bali, namely jengah (a shame that arouses enthusiasm for achievement); taksu (inner spirit or aura that supports someone in his/her profession or jobs); manyamabraya (the spirit of brotherhood and social confession that we are brothers). This research explains the impacts of local cultural values-based organizational culture on the job stress and performance of cooperatives employees in Bali. This study uses a quantitative approach. The population of this study was cooperatives employees in Bali, with a total of 22.067 people in 2017. The analysis technique uses SEM-PLS.The results show that organizational culture based on Balinese cultural values has a negative and significant effect on employee job stress, an organizational culture based on Balinese cultural values has a positive and significant effect on organizational performance, and job stress has a negative and no significant effect on performance. This study found that a strong local culture values-based organizational culture reduces employee stress and improves employee performance